Faktor- Faktor yang Mempengaruhi Tingkat Profitabilitas Bank Umum Syariah Di Indonesia - Muryani Arsal; Andi Musyarrafah Rusli; Ismail Badoahi (Owner : Riset dan Jurnal Akuntansi, 2025)
This aims of study to examine the effect of financial ratios which is Capital Adequacy Ratio (CAR), Operating Costs Operating Income (BOPO), Non Performing Financing (NPF), Financing to Deposit Ratio (FDR), and Inflation Rate on profitability in Sharia Commercial Banks in Indonesia for the 2018-2022 period. This research used quantitative research where using secondary data from the financial reports of Sharia Commercial Banks. The data analysis technique used is multiple linear regression. The research results show that BOPO, NPF, and FDR have a significant effect on profitability, while CAR and the Inflation Rate do not have a significant effect. This research contributes to understanding the factors that influence the profitability of Sharia Commercial Banks in Indonesia, so that it can be a consideration for management in making strategic decisions regarding financial management and bank operations.